Analisis Faktor-Faktor Yang Mempengaruhi Indeks Prestasi Kumulatif (IPK) Mahasiswa Program Studi Kesejahteraan Sosial Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Ar-Raniry - Adha Sunardi Adha (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
During their studies, students often experience several factors that influence their learning achievement. Factors that influence learning outcomes are divided into two, namely internal factors and external factors. Internal factors relate to everything related to oneself in the form of physiological conditions and psychological conditions. Meanwhile, external factors originate from outside the individual concerned. Therefore, the aim of this research is to determine the factors that influence the Cumulative Achievement Index (GPA) of students in the Social Welfare Study Program, Faculty of Da'wah and Communication, Ar-Raniry State Islamic University. The research uses a qualitative approach with descriptive research methods to explain the ongoing situation. Data collection used observation, interviews and documentation, with 15 informants. The results of the research show that Social Welfare Study Program Students have different economic backgrounds, some of whom work as farmers, laborers, Civil Servants (PNS) and so on. Many Social Welfare Study Program Students decide to study while working. different goals. The main factors that influence students to work are needs factors ranging from basic needs, supporting needs and even lifestyle, so that the aim of improving their knowledge by showing results in the form of a good Grade Point Average (GPA) is put aside. When deciding to study while working, of course students know that they have two responsibilities at once which must be fulfilled optimally